Impact of micro- and nanoplastics exposure on human health: focus on neurological effects from ingestion - Bhattacharyya, Sudeepa; Greer, Melody L.; Salehi, Maryam (Frontiers in Public Health, 2025)
Microplastics (MPs) and nanoplastics (NPs) have become pervasive contaminants in food, water, and air, leading to widespread human exposure, primarily through ingestion. Although MPs are increasingly detected in human tissues, including the placenta, blood, and brain, their long-term health implications are poorly understood. This review compiles emerging evidence on the systemic distribution and biological effects of ingested MPs, particularly on neurological risks. MPs can disrupt gut microbiota, breach intestinal and blood–brain barriers, and accumulate in neural tissues. Mechanistic studies reveal that MPs induce oxidative stress, neuroinflammation, protein aggregation, and neurotransmitter alterations, which may contribute to the development of cognitive dysfunction and neurodegenerative disease pathways. Recent work using brain organoids, single-cell and multi-omics technologies provides deeper mechanistic insights, linking MP/NP exposure to mitochondrial injury, inflammatory signaling, and impaired protein homeostasis. We also identify important gaps in exposure assessment, NPs detection, and epidemiological evidence. Human studies remain scarce but initial reports associating elevated MP/NP burdens in brain tissue with dementia highlight the urgency of this research. To address these gaps, we suggest critical next steps in the research agenda, integrating omics technologies, real-world exposure models, and human-relevant in vitro systems. As MP contamination grows, it is critical to understand its neurotoxic potential for informing public health policy and protecting vulnerable populations.